The Effect of Using Scrabble Games Strategy on EFL Intermediate School Students’ Achievement Motivation and Vocabulary Mastery - Sabah, Fanar Hazim; Sahab, Marwan Mizher (Journal of Tikrit University for Humanities, 2025)
Vocabulary is an important part of English that should be mastered well. It had important role in communication both in spoken and written forms. By having a lot of vocabularies learner will be easier to show many ideas, making compositions, and many activities dealing with language. The present study aims at find out the effect of using scrabble games strategy on EFL intermediate school students’ achievement motivation and vocabulary mastery and explaining the benefits of using it in the educational process through: Finding out the effect of using scrabble game on EFL intermediate school student’s vocabulary mastery and motivation. Finding out whether there is any significant difference between the students’ achievement in the experimental groups’ at the recognition and production levels of the posttest and finding out whether there is any significant difference between the students’ attitudes towards motivation. A sample of (60) students has been randomly selected from Iraqi EFL fourth preparatory school students for Girls from Gamal Abdel Nasser, in Yathrib District, Salah Al-Din, during the academic year (2023–2024). It represents (75) percent of its original population and is divided into two equal groups, i.e., the experimental and control groups. Both groups have been equalized in their age, the parents’ educational achievement, and their degrees in English language subjects in the previous scores of the academic year (2022-2023). The achievement posttest consists of six questions have been developed and tested, their reliability, validity and extended to the two sample classes. The results show that scrabble game strategy is more effective than using the conventional method for organizing, clarifying, or simplifying complex information. Based on the results and obtained conclusions in this work, suitable recommendations and suggestions for further studies are put forward.